Effectiveness of press needle treatment and electroacupuncture in patients with postherpetic neuralgia: A matched propensity score analysis - Patchara Ruengwongroj (2020)
Copyright © 2020 Elsevier Ltd. All rights reserved. BACKGROUND AND PURPOSE: Postherpetic neuralgia (PHN) is a well-known painful syndrome. Acupuncture is a treatment for PHN. We aimed to compare the effectiveness of pain control between press needle and electroacupuncture (EA) in PHN patients. MATERIALS AND METHODS: We conducted a retrospective cohort study by a review of PHN patients treated with the press needle and the EA and compared the Pain visual analogue scale (VAS) before and after treatment. Propensity score matching was applied to adjust the confounding. RESULTS: 48 patients in each group had a matched propensity score. The absolute reduction of VAS in the press needle and the EA groups were not different (5.4±2.8 vs. 5.4±2.9, p=0.971). The VAS score improvement was not statistically different between groups. CONCLUSION: The Press needle and the EA are equally effective in the treatment of PHN.